Analysis Distribution and Affordability of Educational Field Practices Geography Education Students - Mariya, Sri; Anwar, Syafri; Suasti, Yurni; Wirda, Mona Adria (Universitas Negeri Padang, 2024)
This research aims to analyze the distribution and accessibility of educational field practice (PLK) locations as places where teaching by Geography Education Field Practice students in Padang City. The method used in this research is the euclidean distance method to estimate and reflect the direct distance between the locations of schools by measuring the distance to school points (maximum and minimum) which tend to be the goals of PLK activities in Padang City from 2021 to 2023. Analysis carried out carried out divided into sub-district areas in Padang City. The results of analysis distribution of PLK location selection are spread across several schools in eleven sub-districts. The affordability of location shows that there are differences in the geographical distribution of educational field practice schools in Padang City. Distribution of maximum and minimum distance variations between schools and between different sub-districts through analysis with the help of the Geography Information System. The results of the affordability analysis explain that there is a difference between the maximum and minimum distance between schools and the number of students who choose teaching practice locations from the outermost area of the sub-district. Where areas closer to school points are an option for prospective PLK students.